Effects of dipeptidyl peptidase‐4 inhibition in an animal model of experimental asthma: a matter of dose, route, and time. Issue 5 (2nd October 2013) - Stephan, Michael; Suhling, Hendrik; Schade, Jutta; Wittlake, Mareike; Tasic, Tihana; Klemann, Christian; Pabst, Reinhard; Jurawitz, Marie‐Charlot; Raber, Kerstin A.; Hoymann, Heinz G.; Braun, Armin; Glaab, Thomas; et al.
Abstract: The CD26‐associated enzymatic activity of dipeptidyl peptidase‐4 (DPP4) as well as the recruitment of CD26 + T cells increase under allergic airway inflammation. Furthermore, genetic deficiency of CD26/DPP4 exerts protective effects in experimental asthma. Therefore, CD26/DPP4 might represent a novel therapeutic target in asthma. To study the effects of pharmacological inhibition of DPP4 on allergic airway inflammation the DPP4‐inhibitor isoleucine thiazolidide was tested using different doses at different time points (at sensitization, immediately before and simultaneously with the allergen challenge, as well as continuously via drinking water), and different routes (intraperitoneal, oral, and by inhalation). Allergic‐like airway inflammation was induced in Fischer 344 rats (Charles River) sensitized against ovalbumin (OVA) using OVA aerosols. Intraperitoneal application of the DPP4 inhibitor showed effects neither at sensitization nor at challenge, whereas a continuous application via drinking water using high doses of the inhibitor led to an aggravation of the histomorphological signs of airway inflammation. In contrast, aerosolization of the DPP4 inhibitor simultaneously with the allergen significantly reduced airway hyperresponsiveness and ameliorated histopathological signs compared to controls. In addition, this treatment resulted in increased mRNA levels of surfactant proteins, suggesting an involvement of DPP4 inhibitors in surfactant metabolism in OVA‐challenged rats. Continuous systemic inhibition of DPP4 via the oral route aggravates allergic airway inflammation. In contrast, topical inhibition of DPP4 exerts potential protective effects, and further research in humans is needed. Abstract : e00095 Abstract : This article focuses on alteration of asthmatic allergic reaction using a CD26/DPP4 (dipeptidyl peptidase‐4) inhibitor in a rat model of asthmatic inflammation. This study proves different effects on clinical signs and cellular inflammation depending on the route of drug administration (chronic via drinking water or inhaled). Aerosolization of the DPP4 inhibitor simultaneously with the allergen significantly reduced airway hyperresponsiveness and ameliorated histopathological signs compared to controls.